Protoplast: A Valuable Toolbox to Investigate Plant Stress Perception and Response - Gilliard, Guillaume; Huby, Eloïse; Cordelier, Sylvain; Ongena, Marc; Dhondt-Cordelier, Sandrine; Deleu, Magali (Frontiers in Plant Science, 2021)
Plants are constantly facing abiotic and biotic stresses. To continue to thrive in their environment, they have developed many sophisticated mechanisms to perceive these stresses and provide an appropriate response. There are many ways to study these stress signals in plant and among them, protoplasts appear to provide a unique experimental system. As plant cells devoid of cell wall, protoplasts allow observations at the individual cell level. They also offer a prime access to the plasma membrane and an original view on the inside of the cell. In this regard, protoplasts are particularly useful to address essential biological questions regarding stress response, such as protein signalling, ion fluxes, ROS production, and plasma membrane dynamics. Here, the tools associated with protoplasts to comprehend plant stress signalling are overviewed and their potential to decipher plant defence mechanisms is discussed.